Adoption of Cash on delivery (COD) Payment System in Tokopedia Marketplace Transaction - Nurul Aulia Ramadhina; Arry Widodo; Nurafni Rubiyanti; Anita Silvianita (Formosa Journal of Multidisciplinary Research, 2024)
Everyone is connected to the internet, everyone now trusts buying and selling activities on the internet, and currently the internet world has sufficient security. The growth of marketplace platforms such as Tokopedia makes it easier for people to make purchases just from home. The Cash on Delivery (COD) payment system is an option for people who want easy direct payments. The COD payment method has many benefits, especially in avoiding fraud. Apart from having advantages, the COD system also has disadvantages, one of which is that customers do not want to pay for the products sent and blame the courier. This conceptual paper uses the UTAUT development theory. The sampling technique in this study used nonprobability sampling. This technique is a sampling technique that is selected based on subjective judgment. The sampling method used is purposive sampling. The sample in this study were consumers who have used and purchased green cosmetic products in Indonesia. The research model used is Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach.